Development of Tools for Live Networked Musical Performance System using Smartphones - Alexandre Resende Clément (2015)
This thesis work contemplates the development a suite of Pure Data tools, as well as their integration into mobile applications via libPD, as part of a larger project encompassing the design and implementation of a system allowing for interaction between performer and audience via smartphones. The "Bridging the gap between performers and the audience using networked smartphones" project, henceforth referenced in this document by its working name - "Abel", aims to provide artists with a way to easily interact with their audience, making use of their input to effectively craft unique performances. This toolset consists of a series of custom-built Pure Data externals developed in C, accompanied with corresponding helper patches to illustrate their use. Using the developed suite, multimedia artists can easily create and distribute interactive content unto mobile devices by means of this networked system, without any additional expertise other than normal Pure Data content creation, providing them with a familiar and immediate way of using this system.